Comparison of domains of self-reported physical activity between Kenyan adult urban-slum dwellers and national estimates. Issue 1 (1st January 2017) - Groot, Hilde E.; Muthuri, Stella K.
ABSTRACT: Background : Non-communicable diseases (NCDs) – largely the result of modifiable behavioral risks such as physical inactivity that gradually develop into physiological risks – are a main cause of morbidity and mortality worldwide. In Kenya, a nationally representative STEPwise survey of risk factors for NCDs established that 10.8% of Kenyans accumulated low levels of total physical activity. Objectives : The goal of our analyses was to compare domains of self-reported physical activity in two Nairobi slums to national estimates. Methods : Levels and time of self-reported activity in three domains (work, transport, and recreation), collected as part of a SCALE-UP study conducted in Korogocho and Viwandani slums in Nairobi, were compared to STEPwise findings. Results : The samples included a total of 10, 128 participants (5, 628 slum, 4, 500 national). Only 7.1% and 4.0% of slum dwellers reported low levels of work and transport physical activity, respectively, but 95.9% reported low levels of recreation-related activity. Slum residents reported higher mean daily minutes of total activity than the national estimate (499 minutes versus 291 minutes), however, both samples spent similar proportions of total activity on work (79.0% slum, 78.3% national), transport (20.4% slum, 18.1% national), and recreation (0.6% slum, 3.6% national) activities. Conclusions : While the total amount of time spent in different domains of self-reported activity differs between urban slum residents and the national Kenyan population, proportions of time in each of the three domains are similar. It is important that such differences or similarities be considered when addressing NCD risk factors in these populations.